2019
DOI: 10.7567/1347-4065/ab0436
|View full text |Cite
|
Sign up to set email alerts
|

Control of molecular orientation in a single-molecule junction with a tripodal triptycene anchoring unit: toward a simple and facile single-molecule diode

Abstract: We report a simple and facile procedure to control molecular orientation in a single-molecule junction and relevant rectification properties. Rectification properties of single-molecule junctions consisting of tripodal triptycene and C 60 moieties at the termini that couple to the Au electrodes were determined using the break junction method. Because of the strong affinity of the tripodal triptycene moiety to the Au electrode, the molecular orientation and the related rectification direction are uniquely deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Thus, 1 and 3 can form two major types of molecular junctions. We consider that the higher conduction values result from single-molecule bridges (Figure e), in which both triptycene and TTF (or AQ) subunits on the same molecule are bound to the Au electrodes . The lower conduction profiles arise from bimolecular junctions formed from intermolecular π-stacked homodimers of TTF-TTF (or AQ-AQ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 1 and 3 can form two major types of molecular junctions. We consider that the higher conduction values result from single-molecule bridges (Figure e), in which both triptycene and TTF (or AQ) subunits on the same molecule are bound to the Au electrodes . The lower conduction profiles arise from bimolecular junctions formed from intermolecular π-stacked homodimers of TTF-TTF (or AQ-AQ) .…”
Section: Resultsmentioning
confidence: 99%
“…Molecular electronics is a research field that explores the use of molecules as electronic components in nanoscale devices, combining interdisciplinary research in physics, chemistry, biology, and materials science, and has made remarkable progress over the past two decades. To achieve this goal, the electrical properties of molecules at the single-molecule level have been investigated using self-assembled monolayers (SAMs) and single-molecule junctions of various small organic compounds. Recently, as an evolution of unimolecular systems, the use of π-stacked homodimers as molecular junctions has been demonstrated with a variety of π-conjugated backbones, including phenylene, thiophene, and polycyclic aromatic hydrocarbon systems . It has been reported that such π-stacked dimer junctions exhibit unique charge-transport behaviors, including quantum interference effects, , length-independent tunneling, and structural and electric responsiveness to external electric fields .…”
Section: Introductionmentioning
confidence: 99%
“…The behaviors of single-molecular bridging can be clearly investigated. Using these methods, various functional molecules have been reported, including transistors and PN junctions. However, because structures with controlled gap sizes are individually required for each junction in MCBJ and STMBJ methods, they are disadvantageous for the miniaturization of molecular devices. Therefore, static metal nanogap structures fabricated using only two-faced electrode pairs on immovable substrates, such as Si chips, have been proposed for miniaturization.…”
Section: Introductionmentioning
confidence: 99%
“…4 Breslow proposed the antiaromatic term for molecules having cyclic conjugation with 4np electrons, which are destabilized in comparison to a non-cyclic conjugated reference molecule. 5 The narrow energy gap between the highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) and higher conductivity [5][6][7][8][9] of antiaromatic compounds makes them potential candidates for the design of organic electronic materials, 10 including organic field-effect transistors (OFETs) 9,[11][12][13][14] and organic photovoltaics (OPVs). 13,14 Pentalene and its derivatives are some of the most widely exploited antiaromatic molecules for developing advanced optoelectronic devices.…”
mentioning
confidence: 99%